Value addition through biohydrogen production and integrated processes from hydrothermal pretreatment of lignocellulosic biomass. (February 2023) - Mohanakrishna, Gunda; Modestra, J. Annie
Graphical abstract: Highlights: Biohydrogen production from lignocellulosic biomass has potential for industrial scale. Hydrothermal pretreatment converts lignocellulosic biomass to suitable substrate for biohydrogen production. Selective bioprocess integration improves the energy recovery potential. LCB for biohydrogen production has the potential to develop sustainable biorefineries. Abstract: Bioenergy production is the most sought-after topics at the crunch of energy demand, climate change and waste generation. In view of this, lignocellulosic biomass (LCB) rich in complex organic content has the potential to produce bioenergy in several forms following the pretreatment. Hydrothermal pretreatment that employs high temperatures and pressures is gaining momentum for organics recovery from LCB which can attain value-addition. Diverse bioprocesses such as dark fermentation, anaerobic digestion etc. can be utilized following the pretreatment of LCB which can result in biohydrogen and biomethane production. Besides, integration approaches for LCB utilization that enhance process efficiency and additional products such as biohythane production as well as application of solid residue obtained after LCB pretreatment were discussed. Importance of hydrothermal pretreatment as one of the suitable strategies for LCB utilization is emphasized suggesting its future potential in large scale energy recovery.